Merkel cell polyomavirus (MCV) T-antigen seroreactivity, MCV DNA in eyebrow hairs, and squamous cell carcinoma - Hampras, Shalaka S. (Infect Agent Cancer, 2015)
BACKGROUND: The role of Merkel cell polyomavirus (MCV) infection in the etiology of non-melanoma skin cancers, other than Merkel cell carcinoma, is unclear. Previously, we reported a significant association between seropositivity to MCV capsid antigen and MCV DNA-positive cutaneous squamous cell carcinoma (SCC). Here we present associations between SCC and seroreactivity to MCV T-antigen (T-Ag) oncoprotein, as well as MCV DNA detected in eyebrow hairs. FINDINGS: A clinic-based case–control study, including 171 SCC cases and 300 controls without skin cancer, was conducted at Moffitt Cancer Center in Tampa, Florida. Multiplex assays were used to measure serum antibodies against MCV small and large T-Ag and MCV DNA in both eyebrow hairs and SCC tumors (n = 144). Odds ratios (ORs) and 95 % confidence intervals (CIs) were estimated using logistic regression to evaluate the associations between MCV and SCC. No significant association was observed between seroreactivity to MCV full-length large or small T-Ag and SCC, overall [OR(large T-Ag) = 0.99 (0.48-2.08), OR(small T-Ag) = 0.31 (0.06–1.62)] or when comparing tumor MCV DNA-positive cases to controls [OR(large T-Ag) = 1.06 (0.38–2.93)]. Only presence of MCV DNA in eyebrow hairs was significantly associated with MCV DNA-positive SCC [OR = 4.05 (2.01–8.18)]. CONCLUSION: MCV infection is unlikely to play a direct role in SCC.